Malebranche i Locke. Teoria wyboru moralnego, temat zaniedbany - Vienne, Jean-Michel (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 1995)
Malebranche's psychology of error and psychology of moral choice are the core of what Locke kept on admiring, even when criticizing the metaphysics and the theory of ideas underlying them. So to understand why Locke rejects Malebranche's "idea" and Malebranche rejects Locke's "idea", it is useful to see where they agree and disagree in the theory of moral choice: pleasure, supreme good, suspense, uneasiness, desire are themas debated around them (Arnauld, Bayle) and between them.